1999
DOI: 10.1046/j.1365-2222.1999.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of histidine decarboxylase messenger RNA and histamine N‐methyltransferase messenger RNA in nasal allergy

Abstract: Increased HDC mRNA expression and decreased HMT mRNA expression may be playing some role in the hyperresponsiveness of patients with allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
6
20
0
Order By: Relevance
“…Synthesis of histamine by HDC plays another important regulatory step in histamine signaling. HDC mRNA is increased in nasal mucosa of patients with AR (49). The finding that expression of HDC mRNA, HDC activity, and the histamine content of the nasal mucosa were significantly increased after TDI provocation indicates the importance of HDC in allergic responses (13).…”
Section: Discussionmentioning
confidence: 73%
“…Synthesis of histamine by HDC plays another important regulatory step in histamine signaling. HDC mRNA is increased in nasal mucosa of patients with AR (49). The finding that expression of HDC mRNA, HDC activity, and the histamine content of the nasal mucosa were significantly increased after TDI provocation indicates the importance of HDC in allergic responses (13).…”
Section: Discussionmentioning
confidence: 73%
“…Many studies have shown that activation of H1R by histamine is responsible for the symptoms of allergic rhinitis, including sneezing, watery rhinorrhea, and nasal itching, and the high efficacy of antihistamines in controlling nasal hypersensitivity symptoms in the eliciting/effecter phase of nasal allergy (34 -37). In eukaryotes, HDC is the sole enzyme responsible for synthesizing histamine and consequently regulation of the HDC activity is a crucial step for histamine biosynthesis (38).…”
Section: Introductionmentioning
confidence: 99%
“…HDC mRNA expression was increased in the nasal mucosa of Japanese patients with allergic rhinitis compared to those without the disease [17]. A study by Gervasini, et a.l, which included HDC nonsynonymous SNPs, (HDC 1932 A/C (Glu644Asp, rs2073440) and HDC 92C/T (Thr31Met, rs17740607)) and newly identified synonymous SNPs (rs854163, rs35047996) was conducted in a well-defined allergic phenotype population of Caucasian subjects from Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional significance of many of these SNPs is unknown, several studies have been conducted to explore potential associations between histamine related genes and asthma and allergic disease [6,17,[33][34][35][36][37][38][39][40][41][42][43]. We have previously reported that the HRH1 gene was more highly expressed in buccal tissue from those with asthma compared to those without asthma [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation